2016
DOI: 10.1042/bcj20160271
|View full text |Cite
|
Sign up to set email alerts
|

Two insulin-like peptides differentially regulate malaria parasite infection in the mosquito through effects on intermediary metabolism

Abstract: Insulin-like peptides (ILPs) play important roles in growth and metabolic homeostasis, but have also emerged as key regulators of stress responses and immunity in a variety of vertebrates and invertebrates. Furthermore, a growing literature suggests that insulin signaling-dependent metabolic provisioning can influence host responses to infection and affect infection outcomes. In line with these studies, we previously showed that knockdown of either of two closely related, infection-induced ILPs, ILP3 and ILP4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 76 publications
1
27
0
Order By: Relevance
“…falciparum resistance in A . stephensi [22], so this approach was chosen to help us define the nature of parasite resistance associated with JNK inhibition. While our data suggested that MKP4 activity is likely specific to JNK signaling in the A .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…falciparum resistance in A . stephensi [22], so this approach was chosen to help us define the nature of parasite resistance associated with JNK inhibition. While our data suggested that MKP4 activity is likely specific to JNK signaling in the A .…”
Section: Resultsmentioning
confidence: 99%
“…Resistance was independent of effects on NF-κB-dependent innate immunity, adding to the list of similar observations in A . stephensi that highlight the importance of alternative signaling pathways and intermediary metabolism in mediating anti-parasite resistance [14, 20, 22]. The phenotypic effects of JNK inhibition may be due in part to inhibition of IIS in the A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether ABA activates these pathways to regulate host immunity, we examined insulin-like peptide ( ilp ) gene expression, which is regulated by IIS [12], as well as activation of the MAPKs ERK, JNK, and p38 MAPK and the MAP3K TAK1 in the A. stephensi midgut. We focused our analyses on ILP3 and ILP4, which regulate P. falciparum development in A. stephensi through effects on midgut intermediary metabolism and mitochondrial function [13]. In contrast to ABA enhancement of insulin secretion in mammalian cells, ABA significantly repressed expression of ilp3 mRNA at 8 h post-infection ( t  = 2.953, df  = 6, P  = 0.026) and ilp4 mRNA at 4 ( t  = 3.472, df  = 5, P  = 0.018), 6 ( t  = 13.42, df  = 5, P  < 0.0001), and 8 ( t  = 3.079, df  = 6, P  = 0.022) hours post-infection in the mosquito midgut relative to controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A reduction of trehalose level by knocking down trehalose transporter, AgTret1, impaired Plasmodium falciparum infection in mosquitoes . Insulin/insulin-like growth factor signaling (IIS) is also involved in regulating of Plasmodium falciparum infection in mosquitoes (Corby-Harris et al, 2010;Luckhart et al, 2013;Pietri et al, 2016). Thus, glucose metabolism in mosquito is expected to play a role in the development of Plasmodium parasites.…”
Section: Introductionmentioning
confidence: 99%